PLEAAAAASEEE HEEEELPPPPP!!!! ILL GIVE BRAINLIEST!!!!
![PLEAAAAASEEE HEEEELPPPPP ILL GIVE BRAINLIEST class=](https://us-static.z-dn.net/files/d15/5141c1a9aba835e9a29573d57d012f55.png)
![PLEAAAAASEEE HEEEELPPPPP ILL GIVE BRAINLIEST class=](https://us-static.z-dn.net/files/d3a/deb3baad8c1f3a1ded7a312b523c271f.png)
Answer:
See below
Step-by-step explanation:
[tex] \huge {4}^{3}. (3 \sqrt{16} )^{ - 2} \\ \\ = \huge 64. (3 .4 )^{ - 2}\\ \\ = \huge 64. (12)^{ - 2} \\ \\ = \huge \frac{64}{(12)^{ 2}} \\ \\ = \huge \frac{64}{144} \\ \\\huge = \frac{4}{9} \\ \\ \\ \huge( {a}^{5} . {a}^{ - 2} )^{3} \\ \\ = \huge( {a}^{5 - 2} )^{3} \\ \\ = \huge( {a}^{3} )^{3} \\ \\ = \huge{a}^{3 \times 3} \\ \\ = \huge{a}^{9} [/tex]